Pengaruh Profitabilitas, Kepemilikan Manajerial dan Karakter Eksekutif terhadap Nilai Perusahaan : Studi pada Perusahaan Manufaktur di Bursa Efek Indonesia Tahun 2016-2021 - Erawati, Teguh; Al Ghafuur, Feby (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of profitability, managerial ownership and executive character on firm value. The sample used in this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) for 2016-2021. Sampling in this study used a purposive sampling method and obtained 22 companies with data processed from 123 annual financial reports. The data analysis method used is multiple linear regression analysis. The results in this study state that profitability has a positive effect on firm value, managerial ownership does not have a positive effect on firm value, executive character has a positive effect on firm value.